2007 IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks 2007
DOI: 10.1109/wowmom.2007.4351727
|View full text |Cite
|
Sign up to set email alerts
|

Platform for Emulating Networked Control Systems in Laboratory Environments

Abstract: ter collisions (see e.g.[1], [3]). Such deficiencies are difficult for traditional control algorithms to handle. Often the This paper discusses a platform for prototyping control control algorithms assume constant sampling intervals and schemesfor networked control systems (NCS). The platform do not consider such asynchronic systems.provides tools for simulating various networks in connecAs the interest of automation industry rises towards diftion with real processes. The paperfocuses on an extension ferent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 4 publications
0
19
0
2
Order By: Relevance
“…PiccSIM [9] is a joint network and control simulation tool that combines MATLAB and Simulink with the ns-2 simulator. After extending it to support mobility, authors of [10] applied PiccSIM to realistic simulations of a mobile robot squad.…”
Section: Related Workmentioning
confidence: 99%
“…PiccSIM [9] is a joint network and control simulation tool that combines MATLAB and Simulink with the ns-2 simulator. After extending it to support mobility, authors of [10] applied PiccSIM to realistic simulations of a mobile robot squad.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, research activities in the eld of wireless real-time technologies for NCSs have been very active as testied by the relevant amount of literature produced on this subject, by the number of developed simulation/experimentation platforms (Andersson et al, 2005;Cervin et al 2007;Hasan et al, 2007;Nethi et al, 2007;Biasi et al, 2008;Chen et al, 2008), and by the already available communication technologies (Neumann, 2007;Pellegrini et al, 2006;Willig et al, 2005) for WNCSs. Herein, it follows a review of the most important contributions that are related to our discussion.…”
Section: State Of the Art On Wireless Real-time Systemsmentioning
confidence: 99%
“…PiccSIM stands for Platform for integrated communications and control design, simulation, implementation and modelling (Nethi et al, 2007) and is developed at Aalto University School of Science and Technology (PiccSIM, 2010). PiccSIM integrates two simulators to achieve an accurate and versatile simulation system at both the communication and control level for WiNCSs.…”
Section: Piccsimmentioning
confidence: 99%
“…For further details see (Nethi et al, 2007), where the integration of ns-2 and Simulink is reported, and (Kohtamäki et al, 2009;Pohjola et al, 2005). Packets sent over the simulated network are routed through the ns-2 computer, which simulates the network in ns-2 according to any TCL script specification generated automatically by a network configuration tool.…”
Section: Piccsim Architecturementioning
confidence: 99%